Depatriarchalize teaching: contributions of Sexual Education to think a counter-Didactics (Praxis Educativa, 2024)
This presentation summarizes the evolution of my experience as a Biology teacher, which starts from a traditional perspective of teaching the discipline towards the search for new paradigms – antipatriarchal, antiability and intercultural- didactic by the hand of Sexual Education (ESI). Contributions are taken from feminist thought and from other social groups produced in various historical and political contexts that question knowledge and knowledge given from the recognition of the persistence of the coloniality of power-knowledge, that is, of a hierarchy imposed by the axes of power of race, social class, sex-gender, among others, fundamentally, in the educational field. The intersectional paradigm of ESI is proposed in the creation of didactic devices for the construction of a counter-hegemonic didactics, that is, a counter-Didactics. It should be sought in those places where it is possible to “rethink what is crystallized and naturalized to build other teaching proposals, based on equality as a starting point” (Ramírez, 2023:4). That is the place of the ESI.
Keywords: didactic against hegemonic; ESI; localized didactic devices; intersectionality